Доклад Генерального секретаря о работе Организации 2024 год - United Nations (United Nations, 2024)
The Report of the Secretary-General on the Work of the Organization (A/79/1) is issued in response to Article 98 of the UN Charter and highlights how the UN Secretariat translates resources into impact. The Report covers nine sections: (i) forging pathways for sustainable development; (ii) fostering peace and security; (iii) propelling African growth; (iv) upholding human rights; (v) securing humanitarian assistance; (vi) advancing justice and international law; (vii) championing disarmament; (viii) combating drugs, crime and terrorism; and (ix) enhancing our operations. The e-book for this publication has been converted into an accessible format for the visually impaired and people with print reading disabilities. It is fully compatible with leading screen-reader technologies such as JAWS and NVDA.